Sedentary behavior and physical activity on exercise capacity in adult patients with congenital heart disease - Masahiro Matsui; Keisei Kosaki; Naoto Kawamatsu; Yoshihiro Nozaki; Tomoko Machino-Otsuka; Yoshio Nakata; Seiji Maeda; Tomoko Ishizu (International Journal of Cardiology Congenital Heart Disease)
Background: Reduced exercise capacity is associated with a poor prognosis in adult patients with congenital heart disease (CHD). Reducing sedentary behavior (SB) and increasing physical activity (PA) could be potential strategies that may contribute to enhanced fitness and prevention of acquired cardiovascular disease in adult patients with CHD. The present study aimed to examine the association of SB and PA with exercise capacity in adult patients with CHD. Methods: Ninety-six adult patients with CHD (age: 18–74 years) underwent measurements of peak oxygen uptake (VO2), % predicted peak VO2, and time spent in SB, light physical activity (LPA), and moderate-to-vigorous physical activity (MVPA). Three regression models (single-activity, partition, and isotemporal substitution) were used to examine the associations of the time spent in SB, LPA, and MVPA with peak VO2 and % predicted peak VO2. Results: In the single-activity and partition models, time spent in MVPA was consistently associated with peak VO2 and % predicted peak VO2. The isotemporal substitution model indicated that replacing 10-min of SB with the same duration of MVPA was associated with a higher peak VO2 (by 0.454 mL/min/kg [0.100 mL/min/kg, 0.807 mL/min/kg]) and % predicted peak VO2 (by 1.810 % [0.594 %, 3.026 %]). Conclusion: These findings suggest that reducing SB time and increasing PA time are associated with improved exercise capacity in adult patients with CHD.